Role of Administrator in School Improvement at Secondary School Level: A Qualitative Study - Mustafa, Ghulam; Hassan, Khawaja Hisham Ul; Akmal, Farhana (Pakistan Journal of Humanities and Social Sciences, 2023)
School improvement is a critical aspect of any educational system, and administrators play a significant role in achieving this goal. The purpose of this qualitative research study was to explore the role of administrators in school improvement at the secondary level. The study used semi-structured interviews and document analysis to gather data from a sample of secondary school administrators. The study's findings indicated that administrators played a critical role in school improvement through their leadership, communication, and decision-making. They also faced several challenges, including limited resources, resistance to change, and lack of support from stakeholders. The study concluded by recommending strategies that administrators can adopt to overcome these challenges and enhance their effectiveness in school improvement.